2021
DOI: 10.3748/wjg.v27.i25.3762
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatitis B virus infection in patients with inflammatory bowel disease under immunosuppressive treatment

Abstract: Hepatitis B remains a significant global clinical problem, despite the implementation of safe and effective vaccination programs. The prevalence of hepatitis B virus (HBV) in patients with inflammatory bowel disease (IBD) largely follows the regional epidemiologic status. Serological screening with hepatitis B surface antigen (HBsAg), and antibodies to hepatitis B surface (anti-HBs) and core (anti-HBc) proteins is a key element in the management of IBD patients and, ideally, should be performed at IBD diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 100 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…In anti-HBc positive patients, antiviral prophylaxis can be proposed particularly for treatments at high risk of reactivation [ 3 , 9 ]. Non-immunized patients should be proposed vaccination at the time of IBD diagnosis and before initiating immunomodulatory treatment [ 2 , 10 ]. Yet, this patient benefited from a correct full vaccine scheme a few years earlier as reported in his medical file.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In anti-HBc positive patients, antiviral prophylaxis can be proposed particularly for treatments at high risk of reactivation [ 3 , 9 ]. Non-immunized patients should be proposed vaccination at the time of IBD diagnosis and before initiating immunomodulatory treatment [ 2 , 10 ]. Yet, this patient benefited from a correct full vaccine scheme a few years earlier as reported in his medical file.…”
Section: Discussionmentioning
confidence: 99%
“…Early vaccination, before immunosuppressive treatment initiation is preferable as the HBV vaccine response rate in patients using immunomodulators is dramatically decreased, in particular in infliximab-users, even with high dose vaccine [ 12 , 13 ]. An anti-HBs titer above 10 IU/L such as recommended in healthy individuals may not be sufficient for IBD patient; the definition of a minimal threshold in such situation would be useful [ 10 ]. Thus, efforts should be made to vaccinate IBD patients against HBV or to give a booster dose to maintain high anti-HBs Ab levels before immune suppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Hepatitis B virus incidence in individuals with IBD in many countries is reported to closely reflecting the general public epidemiologic status. 46 HBV infection has been reported to cause fulminant or fatal hepatitis in IBD patients due to opportunistic infection or reactivation of HBV, but it is prevented with a vaccine. 47,48 The nature of the disease, immunosuppressive medications such as biologics and immunomodulators, and procedures such as endoscopy, transfusion, and surgery, which are frequently necessary during treatment, all enhance the risk of infectious disease in patients with IBD.…”
Section: Hepatitis B Vaccinementioning
confidence: 99%
“…Its prevalence has altered over the past 30 years because of immigration, socioeconomic progress, and the introduction of a vaccine. Research in Europe, Asia, and the Americas has identified a varied range of HBV prevalence in IBD patients, ranging from 0.5% to 15% [8]. In 2016, the World Health Organization (WHO) invited all countries to collaborate in a campaign aiming to eradicate viral hepatitis, including HBV, by the year 2030 [9].…”
Section: Introductionmentioning
confidence: 99%